Sortase-mediated immobilization of Candida antarctica lipase B (CalB) on graphene oxide; comparison with chemical approach - Faezeh Moosavi; Faezeh Ahrari; Gholamreza Ahmadian; Mehdi Mohammadi (Biotechnology Reports, 2022)
In this study, Candida antarctica lipase B (CalB) was covalently immobilized on the surface of graphene oxide (GO) nanoparticles by sortase-mediated immobilization as well as a chemical attachment approach. Sortase is a transpeptidase that provides one-step purification and targeted immobilization of CalB from one specific site, presenting oriented attachment of the enzyme to a solid support. Chemical immobilization, on the other hand, is considered as a random immobilization, in which the protein can bind to the support from different regions of the protein surface. In this approach, amine-functionalized GO was further modified with glutaraldehyde to facilitate the covalent binding of CalB via its amine residues. The applied methods produced 60% and 100% immobilization yields and presented 0.106 U/mg and 0.085 U/mg of specific activities for the oriented and random immobilization, respectively. The stabilized enzyme with the sortase-mediated approach retained approximately 80% of its initial activity at 50°C.